'But That's Not Evidence; It's Not Even True!'. (17th December 2012) - Leite, Adam
<x xml:space="preserve">Abstract</x> If p is false, it isn't evidence for anything. This view is central in one important response to a familiar sceptical argument. I consider and reject various motivations for refusing to accept this view – proposals arising from, e.g., our practice of providing rationalising explanations of people's beliefs, various locutions appearing to relativise evidence to persons, the significance of people's mental states for attributions of reasons to them, and the role of evidence in epistemic principles and requirements. I close by considering responses to the 'New Evil Demon Argument'. What emerges is an affirmation of the principle that p doesn't provide evidence unless it is true, a response to an important version of the Evil Demon argument for scepticism, and also a deeper interpretation of our epistemic practice.